Dynamics and heterogeneity of subjective stock market expectations - Florian Heiss; Michael D. Hurd; Tobias Rossmann; Joachim Winter; Maarten Van Rooij (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Between 2004 and 2016, we elicited individuals' subjective expectations of stock market returns in a Dutch internet panel at bi-annual intervals. In this paper, we develop a panel data model with a finite mixture of expectation types who differ in how they use past stock market returns to form current stock market expectations. The model allows for rounding in the probabilistic responses and for observed and unobserved heterogeneity at several levels. We estimate the type distribution in the population and find evidence for considerable heterogeneity in expectation types and meaningful variation over time, in particular during the financial crisis of 2008/09.
Keywords: D12; D84; G11; 330; expectations; stock markets; financial crisis; mixture models; surveys